Build Skill Literacy of Early Child with Storytelling - Purwasih, Wahyu (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2018)
Every child has a literacy device that he has brought from birth. The literacy device is the abilityto read, write, and put ideas into writing. The first step taken by educators to develop children'sliteracy is by providing various interesting books and giving children the opportunity to flipthrough the book. One of the problems faced by some PAUD institutions today is thedevelopment of children's literacy skills by drill. This actually makes children more depressedand bored of going to school. Finally, the child is just smart to read, but does not love reading.Implementation of storytelling activities in PAUD institutions is able to develop children'sliteracy skills without coercion and in a pleasant atmosphere. This is indicated by children'sinterest in books when children are routinely read stories